MULTIDISCIPLINARY APPROACH FOR OPTIMAL GROWTH AND DEVELOPMENT IN CHILDREN WITH CRANIOFACIAL AND MANDIBULAR ANOMALIES - Sidonia Susanu; Mara Popescu; Laura Mihaela Trandafir; C. Paiu; Alina Belu (Romanian Society of Oral Rehabilitation, 2019)
Craniofacial congenital anomalies may involve skull, orbits, forehead, nose, maxilla, mandible, ears, tongue and lips and impose many problems (clinical, psychological, behavioural, social), especially among children. All these anomalies cause clinically secondary issues such as airway obstruction, respiratory problems, feeding problems, ear disease, distal systemic issues, and speech and communication problems. Children dealing with these disorders do not only need a surgeon to correct the problem but also a multidisciplinary team to provide an accurate assessment, a correct diagnosis, and proper management.